Persistence of positive Brucella Melitensis blood cultures is not associated with focal infection - Meir Cherniak; Matan J Cohen; Yonatan Oster; Daniel Grupel (International Journal of Infectious Diseases)
Objectives: Brucellosis is a global zoonotic disease complicated by focal infections requiring treatment modifications. In other bacterial infections, persistent positive blood cultures prompt evaluation for metastatic foci. We aimed to assess whether persistent bacteremia predicts focal infections in patients with Brucella melitensis infection. Methods: We conducted a retrospective cohort study from 2010 to 2022. We included adults hospitalized due to Brucella melitensis bacteremia. Patients were categorized into persistently positive (PFUBC), negative (NFUBC), or no follow-up cultures. The primary outcome was focal infection (FI). Results: Of 108 patients included, 74.8% exhibited persistent bacteremia (PFUBC). FI occurred in 27.8% of cases. Persistent bacteremia was not associated with FI occurrence. Localizing symptoms at presentation strongly predicted FI (OR: 9.4; 95% CI, 3.24-27.4). Among FI-negative patients, PFUBC status was associated with a significant increase in imaging studies (mean 1.8 vs 0.9; P = 0.003) and physician encounters (17.4 vs 11.9; P = 0.012), but did not improve clinical outcomes. Conclusion: Persistently positive blood cultures in B. melitensis bacteremia do not predict focal infections or adverse clinical outcomes but significantly increase healthcare resource utilization without clinical benefit. Clinical symptoms should guide diagnostic evaluations rather than repeated blood cultures.